The role of cultural humility and multicultural competence in school counselors’ social justice advocacy practice: A systematic literature review - Kismawati, Nurul; Nurul Amin, Zakki (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2026)
This study aims to examine the role of cultural humility (CH) and multicultural competence (MC) in shaping school counselors’ social justice advocacy (SJA) practice in Indonesia. This review is motivated by the high potential for intolerance, discrimination, and ideological bias in school settings (Setara Institute, 2023). The study employed a Systematic Literature Review (SLR) method through searches in PubMed, Scopus, Web of Science, ERIC, and PsycINFO, yielding 302 articles. After screening based on the inclusion and exclusion criteria for the years 2015–2025 by two independent reviewers (Cohen’s Kappa = 0.85 and 0.82), 25 articles were selected for analysis. Quality assessment was conducted using the JBI and CASP Checklists (threshold ≥70%), while data synthesis was carried out through open coding, axial coding, and selective coding. The search did not identify any review that simultaneously integrated CH, MC, and SJA within the context of school counselors. The findings indicate that MC serves as the foundation of multicultural knowledge and skills. However, without cultural humility, competence tends to be procedural, whereas CH functions as a reflective dimension that strengthens its implementation. The literature also indicates a relationship between MC–CH integration and SJA practice, although the direction of causality cannot yet be determined. Nineteen of the 25 studies showed that the integration of these two aspects was associated with higher advocacy engagement. These findings may serve as a basis for counselor curriculum development through reflective learning, advocacy simulations, and field practice while considering the Indonesian context. The proposed integrative model remains conceptual and requires further testing through SEM, mediation analysis, or meta-analysis